Cadmium tolerance, distribution, and accumulation in Taraxacum ohwianum Kitam. as a potential Cd-hyperaccumulator. Issue 6 (12th May 2019) - Cheng, Haitao; Liu, Qun; Ma, Ming; Liu, Yue; Wang, Weiting; Ning, Wei
Abstract: Strong capacity of cadmium tolerance and bioaccumulation in dandelions was revealed under 6-month treatments with different Cd concentrations (0, 50, 80, 100, 120 mg/kg). At the lowest Cd concentration (10 mg/kg), bioconcentration factors (BCF) of dandelions were greater than 1 and the transfer coefficient reached the maximum value of 0.74. At the Cd concentration of 100 mg/kg, the biomass of root was the greatest, the aboveground biomass reached 1.73 g/plant DW, which was 1.3 times of the blank control. Cd content in the leaves reached 100.11 mg/kg DW, which was in line with the threshold value (100 mg/kg) of Cd hyperaccumulators. In the roots of dandelions, Cd was mainly stored in the laticifer groups of phloem and cork, and xylem. The important Cd detoxification mechanism of plants included the combination of Cd and cork cell walls, the combination of Cd and xylem parenchyma cells, the combination of Cd and cell inclusions and precipitation in the laticifer. In leaves and scapes, Cd was preferentially accumulated in laticifer, epidermis cell, parenchyma cell inclusions and epidermis appendages, such as non-glandular hairs, etc., indicating that these sites played an important role in detoxification of heavy metals